Two men with dogsled in front of the Yukon Dock Company office, Dawson, Yukon Territory, ca. 1900. - University of Washington Libraries. Special Collections Division
PH Coll 246.223 [Meed journal: "Office and main entrance of Yukon Dock, 1900. My cabin partner Thomas A. Davies was then agent for Dawson & White Horse Navigation Co. operating str. "Lightning" & "Tyrrel"."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number